Trading relationship between burst and transition in kannada stop consonants - T, Rajkumar (Journal of All India Institute of Speech and Hearing)
Speech perception is an area studied since several decades and still remains an unresolved issue. The advancement in the technology and refinement in the approach statergies have helped in gaining more knowledge in this field. Speech signal consist of multi - dimensional cues. This distinct aspect of the speech enables the listeners to distinguish between the speech sounds. Whenever two acoustic cues contribute to the same phonetic distinction/unitary percept, they can be traded off against each otner, with in certain range ie, in the absence of one cue, the other cue takes over and contribute to the perception of the phoneme. This is termed trading relationship.